THE IMPACT OF WORKING CAPITAL, HUMAN RESOURCE COMPETENCE, AND ACCOUNTING INFORMATION SYSTEMS ON THE FINANCIAL PERFORMANCE OF BUMDES Financial Performance of BUMDes - Sarwenda Biduri; Syinja Faridya Anggreini Dwi Wirawan; Sigit Hermawan; Eny Maryanti; Herman Ernandi (Antis Publisher, 2026)
Objective: This study aims to analyze the influence of working capital, human resource competence, and the utilization of accounting information systems on the financial performance of BUMDes in Sidoarjo Regency. Method: The method used in this study is a quantitative method with a causal-associative design, using data collected via questionnaires distributed to 24 BUMDes in the Sidoario and Buduran subdistricts. The data analysis technique used was multiple linear regression, processed using SPSS software. Results: The results of the study indicate that working capital has a significant positive effect, human resource competence has no significant effect, while the utilization of accounting information systems has a significant negative effect on financial performance. Novelty: A Bumdes is an economic institution whose capital is largely owned by the village and whose purpose is to improve the welfare of the village community. In line with its founding purpose, the success of a Bumdes can be measured by the extent to which it is able to contribute to increasing the village’s own revenue (PAS). For a Bumdes to operate optimally, strong financial performance is crucial.